2009
DOI: 10.1007/s10584-008-9543-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate trends of the North American prairie pothole region 1906–2000

Abstract: The Prairie Pothole Region (PPR) is unique to North America. Its millions of wetlands and abundant ecosystem goods and services are highly sensitive to wide variations of temperature and precipitation in time and space characteristic of a strongly continental climate. Precipitation and temperature gradients across the PPR are orthogonal to each other. Precipitation nearly triples from west to east from approximately 300 mm/year to 900 mm/year, while mean annual temperature ranges from approximately 1 • C in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 47 publications
6
127
1
Order By: Relevance
“…Previous research found lakes within the PPR to be important features that commonly experience extensive surface water expansion, subsuming adjacent wetlands during wet periods . These findings suggest that if climate conditions within the US portion of the PPR continue to get wetter, as predicted (e.g., Millett et al, 2009;McKenna et al, 2017), then both small wetland depressions and larger features, such as lakes and floodplains, will both serve critical roles in storing increased inputs of surface water, which could prevent downstream flooding.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Previous research found lakes within the PPR to be important features that commonly experience extensive surface water expansion, subsuming adjacent wetlands during wet periods . These findings suggest that if climate conditions within the US portion of the PPR continue to get wetter, as predicted (e.g., Millett et al, 2009;McKenna et al, 2017), then both small wetland depressions and larger features, such as lakes and floodplains, will both serve critical roles in storing increased inputs of surface water, which could prevent downstream flooding.…”
Section: Discussionsupporting
confidence: 51%
“…This is particularly relevant when we consider the need for communities and local agencies to plan ahead for expected changes in the precipitation regime associated with climate change (Dore, 2005;Johnson et al, 2005;Millett et al, 2009;McKenna et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to widespread forest fires, low water levels in streams, lakes, and reservoirs and low soil moisture levels, and it was unusual in that it stretched over a vast area from Mexico to Alaska. Since the beginning of the 20th century there has been decadal-scale variability in drought occurrence as indicated by various precipitation and soil moisture indices, but there has been no consistent long-term trend in drought frequency or magnitude (Millett et al, 2009;Qian et al, 2010;Bonsal et al, 2013). This variability has tended to coincide primarily with precipitation variations modulated by largescale modes of oceanic-atmospheric circulation Shabbar and Skinner, 2004;Bonsal and Shabbar, 2008).…”
Section: Droughtmentioning
confidence: 99%
“…Warming of Earth's climate is real (IPCC 2014), and there is strong scientific consensus of an anthropogenic cause (Cook et al 2013) with resultant changes already having widespread impacts on natural systems (IPCC 2014). During the past century, the average minimum daily temperature in the PPR has increased by 1°C and precipitation across the region has increased by about 9 % (Millett et al 2009). Global surface temperatures are projected to continue to rise throughout the 21st century (IPCC 2014), influencing water losses from wetlands as evapotranspiration rates change in response to warmer temperatures.…”
Section: Introductionmentioning
confidence: 99%